Piezoelectric induced reverse photocatalytic performances of carbon nitride with different structures. Issue 17 (26th July 2022) - Zhang, Haoqing; Xia, Zhonghui; Niu, Ping; Zhi, Xiaojuan; Dai, Rui; Chen, Silin; Wang, Shulan; Li, Li
Abstract : The piezoelectric properties of graphitic carbon nitride with different structures follow the order PTI > melon > PHI, and the melon and PHI showed reverse activities in the photocatalytic and piezoelectric assisted photocatalytic reactions. Abstract : Piezoelectric assisted photocatalysis has emerged as an effective way to achieve higher utilization of charge carriers through the introduction of an internal electric field. Even though in its infancy, the piezoelectric catalytic properties of graphitic carbon nitride (GCN) have been arousing more and more attention. In this work, the piezoelectric properties as well as the piezoelectric assisted photocatalytic performances of GCN with different structures including melon, poly(heptazine imide) (PHI) and poly(triazine imide) (PTI) were investigated in detail. The PTI constructed from triazine units shows the best piezoelectric catalytic performances in the typical potassium permanganate (KMnO4 ) reduction and the hydrogen peroxide (H2 O2 ) generation reactions under ultrasonication. Interestingly, the melon and PHI showed reverse activities in the photocatalytic and piezoelectric assisted photocatalytic reactions due to their different piezoelectric properties. The in situ deposition of Au particles (around 100 nm) by piezoelectric reduction of HAuCl4 and the finite element analysis were included to reveal the distinctive piezoelectric properties. This work may inspire more attempts to modify the piezoelectric properties of GCN and extend the photocatalytic applications of GCN with the assistance of piezoelectric properties.